Video Profil Daerah Sebagai Media Informasi Infrastruktur dan Tata Ruang Kota Gresik - Galang Asa; Alfian Candra Ayuswantana (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Videos are an electronic medium for conveying information that is very effective. Profile videos can summarize complex information into a concise whole. Regional profile video media is an important instrument in conveying information about a city's infrastructure and spatial planning. This research aims to explore the potential of regional profile video media as an effective means of increasing public understanding regarding the infrastructure and spatial planning of the city of Gresik. Through a qualitative approach and literature study, this research examines various aspects that can strengthen the role of regional profile video media in conveying public information. The research results show that regional profile video media can visualize infrastructure development and city spatial planning. The video can comprehensively depict development projects, combining visual insights with informative narratives. Apart from that, the desire to use regional profile video media can help create a sense of community ownership and involvement in the city development process.